Pelvic Floor Muscle Resting Tone in Children With Dysfunctional Voiding Symptomology Following Simple Gross Motor Exercises. Issue 1 (January 2022) - Berg-Poppe, Patti; Christensen, Monica; Koskovich, Nicole; Stephenson, Christine
Abstract : Purpose: The study aimed to understand the effects of a set of simple gross motor exercises on pelvic floor muscle (PFM) resting tone (RT) in children with dysfunctional voiding symptomology. Methods: The study compared PFM RT for a single-sample before and after 2 protocols: exercise versus relaxation (metric standard). Results: Participants included 27 children ages 5.00 to 10.92 years. Preintervention PFM RT was similar between the interventions: 63% (exercise) and 78% (relaxation) of children decreased PFM RT following intervention. Between-intervention post-minus-prechanges in PFM RT were compared. Between-intervention differences were similar. Conclusions: Exercise and relaxation protocols were comparable in lowering PFM RT in children with voiding dysfunction. Findings are clinically worthy in that either exercises or relaxation prior to toileting may assist with more complete emptying in children with symptoms. Abstract : The study aimed to understand the effects of a set of gross motor exercises on pelvic floor muscle resting tone in children with dysfunctional voiding symptomology